2019
DOI: 10.3389/fmats.2019.00268
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Materials in Promoting Bone Regeneration

Abstract: Strategies to promote bone regeneration have been always the focus of investigations since the skeleton plays important roles like mechanical support, organ protection, and mineral homeostasis maintenance in the normal physiological activities of the human body. Magnetic fields have shown to be highly influential in the regeneration process, arousing tremendous interest in utilizing magnetic materials to enhance osteogenesis. In this work, we attempt a more comprehensive and detailed review of magnetic materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 150 publications
(137 reference statements)
0
34
0
Order By: Relevance
“…Recently, Peng and colleges showed that MNPs activate RUNX-2 mRNA expression and modulate osteoblasts differentiation and promote fracture bone healing. 42 In the presented research, we demonstrated, that MNPs modulate the expression of osteocalcin (Bglap2) and dentin matrix protein 1 (DMP1) axis which are tandem genes involved in new bone formation and calcification. At the same time, the enhanced expression of osteopontin on mRNA as well as protein level was observed in osteoblasts cultivated together with MNPs under MF condition.…”
Section: Dovepressmentioning
confidence: 85%
“…Recently, Peng and colleges showed that MNPs activate RUNX-2 mRNA expression and modulate osteoblasts differentiation and promote fracture bone healing. 42 In the presented research, we demonstrated, that MNPs modulate the expression of osteocalcin (Bglap2) and dentin matrix protein 1 (DMP1) axis which are tandem genes involved in new bone formation and calcification. At the same time, the enhanced expression of osteopontin on mRNA as well as protein level was observed in osteoblasts cultivated together with MNPs under MF condition.…”
Section: Dovepressmentioning
confidence: 85%
“…The secretion of MtVs under physical stimuli has not been thoroughly investigated, however stimuli such as mechanical forces, electrical and electromagnetic stimulation, ultrasound, shock wave and low-level laser therapy have been shown to promote bone regeneration in vivo and in vitro [ 191 , 192 , 193 ]. These physical stimuli led to increased osteogenesis and bone formation in vivo.…”
Section: Prospect For Therapeutic Applications Of Mtvsmentioning
confidence: 99%
“…Then Maxwell's equations were solved in the frequency domain using the AC/DC module [17,34]. The power which is stored and dissipated by the magnetic implant was derived by using Eq.s (9), whilst the dielectric losses were computed using Eq. (8).…”
Section: Resolution Schemementioning
confidence: 99%
“…Therefore, a plethora of magnetic biomaterials has been developed [4,5,9]. The synthesis of nanocomposites of magnetic nanoparticles (MNPs), polymers or ceramics (for example, using dip-coating or impregnation methods), or the manufacturing of iron-doped bioceramics, is currently under study [9]. Magnetic implants for bone tumour hyperthermia were developed using ferromagnetic or superparamagnetic nanoparticles [5].…”
Section: Introductionmentioning
confidence: 99%